Intestinal obstruction due to an anomalous congenital band - Dimitrios Cyrochristos; George Alexiou; Dimosthenis Ziogas; Nikolaos Xiropotamos (The Saudi Journal of Gastroenterology, 2008)
We report a case of a 20-year-old male who presented with symptoms and signs of intestinal obstruction. The patient reported no previous history of abdominal surgery or trauma while clinical and radiographic examinations were not diagnostic. An open laparotomy was subsequently performed and the intraoperative findings were consistent with a congenital band extending from the antimesenteric wall of the jejunum to the root of mesentery. The band was ligated and divided with an uneventful postoperative course. Congenital bands are extremely rare. Their exact incidence is still unknown and usually observed in childhood. This case, therefore, represents an unusual surgical problem in an older individual in which the diagnosis was clinically unexpected.